2000
DOI: 10.1111/1467-8624.00173
|View full text |Cite
|
Sign up to set email alerts
|

Basic Level Object Categories Support the Acquisition of Novel Adjectives: Evidence from Preschool‐Aged Children

Abstract: Two experiments examined 3- and 4-year-old children's ability to map novel adjectives to object properties. Sixty-four children were introduced to a target (e.g., a bumpy object), and asked to choose between (1) a matching test object (e.g., a different bumpy object), and (2) a contrasting test object (e.g., a smooth object). Four-year-olds successfully extended novel adjectives from the target to the matching test object whether these objects were drawn from the same, or different, basic level categories. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 31 publications
7
83
0
3
Order By: Relevance
“…The Klibanoff and Waxman (2000) results have interesting implications for color-function priming. First, the results suggest that the pound-pour and stir-lift procedures that we have used to date have been effective because the two objects of each exemplar pair (whether spoons or containers) were very similar -in fact they were identical except for their color and the function in which they engaged.…”
Section: The Role Of Comparison In Forming Categorical Event Represenmentioning
confidence: 91%
See 2 more Smart Citations
“…The Klibanoff and Waxman (2000) results have interesting implications for color-function priming. First, the results suggest that the pound-pour and stir-lift procedures that we have used to date have been effective because the two objects of each exemplar pair (whether spoons or containers) were very similar -in fact they were identical except for their color and the function in which they engaged.…”
Section: The Role Of Comparison In Forming Categorical Event Represenmentioning
confidence: 91%
“…For example, Klibanoff and Waxman (2000; investigated the extent to which comparison, and the formation of object categories, influenced the extension of novel adjectives in preschoolers. In one study , 3-and 4-year-olds were shown a target object and the experimenter used a novel adjective to describe the object (e.g., "The horse is blickish.").…”
Section: The Role Of Comparison In Forming Categorical Event Represenmentioning
confidence: 99%
See 1 more Smart Citation
“…If the novel word in the phrase a TIV one is interpreted as an adjective, the child should choose the property match over the kind match. While children under 3-years-old reliably interpret This is a TIV as referring to a category name, they fail to interpret This is a TIV one as referring to a property, extending the novel word to the test object that matches in kind rather than in texture (Hall, 1994;Hall, Waxman & Hurwitz, 1993;Klibanoff & Waxman, 2000;Taylor & Gelman, 1988;Waxman & Kosowski, 1990, Waxman & Markow, 1998. Although consistent with the observation that adjectives are generally harder to learn than nouns, the magnitude and robustness of these negative findings are somewhat surprising given that by 30 months of age English-learning children are typically speaking upwards of 50 descriptive words (Dale & Fenson, 1996).…”
Section: Learning the Meanings Of Adjectivesmentioning
confidence: 98%
“…Akhtar and Montague (1999) demonstrate that children use cross-situational learning to discover the meanings of novel adjectives. Klibanoff and Waxman (2000), furthermore, provide empirical support for their proposal that adjectival categories are learned cross-situationally, within the context of basic level categories.…”
Section: Learning Colour Words Is Slow: a Cross-situational Learning mentioning
confidence: 57%